Textual genres used in universities of Ecuador. What is written in university classes? (Praxis Educativa, 2025)
The objective of this research was to determine the textual genres used by students in 6 Ecuadorian universities along with their writing purposes, through the application of the European Academic Writing Survey, adapted for Ecuador in 1,732 subjects, teachers (31.4%) and students (68.6%). The results reveal that writing is mainly aimed at demonstrating learning and/or understanding of knowledge instead of developing critical reflection, with a reproductive conception of writing. A greater presence of texts from the Disciplinary Knowledge family (Class Notes, Bibliographic Reviews, Written Exams, Summaries) and to a lesser extent Research and Critical Analysis texts was observed. The least used texts were linked to the Personal Reflection family. A strong polysemy was evident in the naming and description of texts, mainly with the textual genres: Essays, Bibliographic Reviews and Research Reports.
Keywords: questionnaire; higher education; academic writing; evaluation; textual genres